Family characteristics as predictors for sexual violence among adolescents in Iceland - Hafdís Guðfinnsdóttir 1995- (2018)
Sexual violence is any kind of sexual act by any person regardless of their relation to the victim. Previous studies have shown that the most common risk factors for child sexual abuse are in the child’s immediate surroundings. These include weak parenting and struggles in the parent-child relationship. The aim of this study was to assess if certain family characteristics (domestic violence, parental control, parental support and family status) can predict sexual violence among adolescents. The data was obtained from the Icelandic Centre for Social Research and Analysis (ICSRA) 2016. The sample included 2042 adolescents aged 16-20 years old. A binary logistic regression analysis showed that less parental support, being a witness or a victim of domestic violence and not living with a parent increases the probabilities of adolescents being sexually violated. Furthermore, when the results were split by gender the results were different, there were different variables that predicted sexual violence among boys and girls. Among boys, being a witness or a victim of domestic violence increased the probabilities of being sexually violated while parental support, parental control and being a victim of domestic violence among girls increased the probabilities of being sexually violated. Key words: sexual violence, parental support, parental control, domestic violence, family characteristics Kynferðisofbeldi er kynferðisleg athöfn sem beinist að einstaklingi gegn vilja hans, framin af einhverjum án tillits til tengsla við fórnarlambið. Fyrri rannsóknir sýna að helstu áhættuþættir kynferðisofbeldis gegn börnum eru þættir úr þeirra nánasta umhverfi. Þessir þættir fela í sér til dæmis lélegar uppeldisaðferðir og slæmt samband forendra og barns. Helsta markmið þessarar rannsóknar var að meta það hvort tilteknir fjölskyldueiginleikar (heimilisofbeldi, eftirlit og stuðningur foreldra, og fjölskylduaðstæður) geti spáð fyrir um að ungmenni verði fyrir kynferðisofbeldi. Rannsóknir og greining útveguðu gögn rannsóknarinnar frá ...